Correlation between thyroidal and peripheral blood total T cells, CD8+ T cells, and CD8+ T- regulatory cells and T-cell reactivity to calsequestrin and collagen XIII in patients with Graves' ophthalmopathy. (2nd October 2018) - Al-Ansari, Farah; Lahooti, Hooshang; Stokes, Leanne; Edirimanne, Senarath; Wall, Jack
ABSTRACT: Purpose/aim of the study : Graves' ophthalmopathy (GO) is closely related to the thyroid autoimmune disorder Graves' disease. Previous studies have suggested roles for thyroidal CD8 +  T cells and autoimmunity against calsequestrin-1 (CASQ)-1 in the link between thyroidal and orbital autoimmune reactions in GO. A role for autoimmunity against CollXIII has also been suggested. In this study, we aimed to investigate correlations between some thyroidal and peripheral blood T-cell subsets and thyroidal T-cell reactivity against CASQ1 and CollXIII in patients with GO. Materials and methods : Fresh thyroid tissues were processed by enzyme digestion and density gradient to isolate mononuclear cells (MNCs). Peripheral blood MNCs were also isolated using density gradient. Flow-cytometric analysis was used to identify the various T-cell subsets. T -cell reactivity to CASQ1 and CollXIII was measured by a 5-day culture of the MNCs and BrdU uptake method. Results : We found a positive correlation between thyroidal CD8 +  T cells and CD8 +  T-regulatory (T-reg) cells in patients with GO. Thyroidal T cells from two out of the three patients with GO tested (66.7%) showed a positive response to CASQ1, while thyroidal T cells from none of the six Graves' Disease patients without ophthalmopathy (GD) tested showed a positive response to this antigen. Thyroidal T cells from these patient groups however, showed no significant differences in their response to CollXIII. Conclusions : Our observations provide further evidence for a possible role of thyroidal CD8 +  T cells, CD8 +  T-reg cells and the autoantigen CASQ1 in the link between thyroidal and orbital autoimmune reactions of GO.